Effect of Hypoxia on the Differentiation and the Self-Renewal of Metanephrogenic Mesenchymal Stem Cells - Shaopeng Liu; Nana Song; Jianqiang He; Xiaofang Yu; Jia Guo; Xiaoyan Jiao; Xiaoqiang Ding; Jie Teng (Hindawi Limited, 2017)
Hypoxia is an important and influential factor in development. The embryonic kidney is exposed to a hypoxic environment throughout its development. The Wnt/β-catenin pathway plays vital roles in the differentiation and self-renewal of metanephrogenic mesenchymal stem cells (MMSCs) from which the kidney is derived. Thus, we hypothesized that hypoxia can regulate the differentiation and pluripotency of MMSCs through the Wnt/β-catenin pathway. To test this hypothesis, MMSCs from rats at embryonic day 18.5 were cultured in normoxic (21% O2) and hypoxic (1% O2) conditions. The effects of hypoxia on differentiation, stemness, proliferation, and apoptosis of cultured MMSCs and on the activity of the Wnt/β-catenin pathway were tested. Our results revealed that the hypoxic condition increased the number of epithelial cells (E-cadherin+ or CK18+) as well the expression of markers of renal tubule epithelia cells (CDH6, Aqp1, and OPN), decreased the number and proliferation of stem cells (SIX-2+ or CITED1+), and induced apoptosis. Additionally, hypoxia reduced the expression of Wnt4 as well as its downstream molecules β-catenin, LEF-1, and Axin2. Activation of the Wnt/β-catenin pathway by LiCl or BIO modified the effects of hypoxia on the differentiation and self-renewal of MMSCs. Thus, we concluded that hypoxia induces the differentiation and inhibits the self-renewal of MMSCs by inhibiting the Wnt/β-catenin pathway. The observations further our understanding of the effects of hypoxia on kidney.